Effects of the addition of thermostable α-amylase on the physicochemical and antioxidant properties of extrusion-pretreated Apios fortunei used for yellow wine fermentation. (15th January 2022) - Bian, Shichao; Zhang, Ruixin; Liu, Qing; Guan, Zhongjing; Jin, Zhengyu; Zhu, Kunfu; Jiao, Aiquan
Abstract: Extrusion-pretreated Apios fortunei was used for yellow wine fermentation. To investigate the effect of thermostable α-amylase on the physicochemical and antioxidant properties of extruded A. fortunei, we used different enzyme concentrations (0–5‰). Enzymatic extrusion increased the degree of gelatinization (84.23–99.99%), water solubility index (28.09–62.75%), reducing sugar content (74.82–263.39 mg/g) and decreased water absorption index (3.25–2.09 g/g) and viscosity (<20 cP) of A. fortunei, these may be beneficial for fermentation . X -ray diffraction and Fourier transform infrared spectroscopy detected that the ordered degree of starch structure decreased with increased enzyme concentration. Molecular-weight analysis indicated that enzyme concentrations of more than 0.5‰ had limited promotion on starch degradation. Scanning electron microscopy observed the eroded surface and holes caused by enzymolysis in enzymatically extruded samples. Enzymatic extrusion increased the phenolic content and antioxidant properties of the samples. Relatively high fermentation efficiency (74.23%) and antioxidant properties (75.87, 76.21 and 203.32 mg of Trolox equivalents/L for DPPH, ABTS and FRAP values, respectively) were observed in wines fermented by extruded samples with 5‰ enzyme. The results indicated that the advantages of enzymatic extrusion in starch degradation and improving the antioxidant properties of A. fortunei could be extended to yellow wine fermentation. Highlights: The ordered degree of starch structure decreased with increased enzyme addition. Enzyme concentrations more than 0.5‰ had limited promotion on starch degradation. The enzyme increased phenolic content and antioxidant properties of Apios fortunei. Apios fortunei treated by enzymatic extrusion was more suitable for fermentation.